PELAKSANAAN PEMUNGUTAN PAJAK DINAS PENDAPATAN DAERAH DALAM MENINGKATKAN PENERIMAAN PAJAK BUMI DAN BANGUNAN DIKOTA PONTIANAK - E.01105123, Markalosenius (PublikA, Jurnal Ilmu Administrasi Negara, 2013)
The title in this research is â€œthe implementation of incomes tax of territory office to improves the collected taxes of earth and construction in pontianak cityâ€. The writer in this thesis have a meaning to express the implementation of taxes by doing of territory office in pontianak city to improves the collected of the taxes in the earth and construction. Still remained to much people is not aware to play a taxes. There are four kinds to implementation the collected of taxes to used. First communication, it is one of programme will be a good to implement if clear to be the implement. The thing have a process to given an information, to got clear information and to given consistent of the information. The second is resources, in here there are four component are total of fulfilment staff and quality of quantity, to get an information to take a decision or arbitrariness to uses enough in the implementation as a responsibility of a task and need a facilities in the implementation. The third is authorizing signature, attitude and commitment of the implementation as a special programme of them to be programme implementation. The fourth is structure of bureaucracy is that sop (standar operating procedures) to put in order method in the programme implementation.Â Key words: The implementation of taxes, collected the taxes, taxes of earth and construction.